Identification of p62/SQSTM1 as a component of non-canonical Wnt VANGL2–JNK signalling in breast cancer - Tania M. Puvirajesinghe (Nature Portfolio, 2016)
Defects in non-canonical Wnt/planar cell polarity signalling have recently been linked to breast cancer aggressiveness. Puvirajesinghe et al. identify VANGL2, p62/SQSTM1 and JNK as important players in this pathway which may be amenable to therapeutic intervention in breast cancer.